2018
DOI: 10.1111/resp.13309
|View full text |Cite
|
Sign up to set email alerts
|

Oesophageal diameter is associated with severity but not progression of systemic sclerosis‐associated interstitial lung disease

Abstract: Oesophageal diameter and hiatal hernia are independently associated with SSc-ILD severity and mortality, but not with ILD progression or asymmetric disease. Oesophageal disease is unlikely to be a significant driver of ILD progression in SSc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…[92][93][94][95][96] In a recently published study of 145 patients with SSc, esophageal dilatation and hiatus hernia were associated with greater degrees of fibrosis on CT and lower baseline FVC, but not disease progression, after correction for these baseline measures. 97 These results confirm those of others which demonstrate that esophageal dilatation is associated with more severe ILD at baseline. 98 Functional measures of esophageal involvement did not predict lung function decline in a recent cohort.…”
Section: The Role Of Reflux In Ssc-ildsupporting
confidence: 91%
“…[92][93][94][95][96] In a recently published study of 145 patients with SSc, esophageal dilatation and hiatus hernia were associated with greater degrees of fibrosis on CT and lower baseline FVC, but not disease progression, after correction for these baseline measures. 97 These results confirm those of others which demonstrate that esophageal dilatation is associated with more severe ILD at baseline. 98 Functional measures of esophageal involvement did not predict lung function decline in a recent cohort.…”
Section: The Role Of Reflux In Ssc-ildsupporting
confidence: 91%
“…In our study, patients with extensive ILD displayed greater tracheal area than patients without pulmonary involvement and patients with limited ILD; all of these patients, in turn, displayed greater tracheal area than the control subjects. Several recent studies have shown that larger esophageal diameter is associated with higher pulmonary fibrosis and worse lung function in individuals with scleroderma [ 35 , 36 ]. Since microaspiration secondary to gastro-esophageal reflux is associated with the progression of pulmonary fibrosis in scleroderma [ 37 , 38 ], we think that the tracheal pathology may also contribute to this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent publication in Respirology , Winstone et al . retrospectively studied the association of hiatal hernia and oesophageal diameter on high‐resolution computed tomography (HRCT) with ILD severity as assessed by HRCT lung fibrosis score, rate of ILD progression measured by decline in lung function and increase in fibrosis on HRCT and mortality in a cohort of 145 patients with systemic sclerosis . The authors found that oesophageal diameter is more than twice as large (mean diameter of 2.3 cm) as in a previous study of normal controls (maximal diameter of 1 mm).…”
mentioning
confidence: 83%
“…Recent studies suggesting that proton pump inhibitor therapy is associated with numerous adverse effects, including increased risk of pneumonia, may prompt reconsideration of their inclusion in routine reflux management . The work of Winstone et al . compels us to conduct rigorous clinical trials to determine the role of microaspiration in the development and progression of ILD.…”
mentioning
confidence: 99%
See 1 more Smart Citation